2019
DOI: 10.1021/acs.jproteome.9b00504
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycan Profile of Cerebrospinal Fluids from Alzheimer’s Disease Patients Using Liquid Chromatography with Mass Spectrometry

Abstract: Glycosylation, an essential post-translational protein modification, is known to be altered in a variety of diseases, including neurodegenerative diseases such as Alzheimer’s disease (AD), which is one of the most common neurodegenerative disorders that results in cognitive and memory impairments. To investigate the progression of such a condition, cerebrospinal fluid (CSF), a unique biofluid that may possess significant biochemical and neurochemical changes due to the disease, is utilized. However, due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 52 publications
1
51
1
Order By: Relevance
“…One issue with this approach has been the fact that the CSF contains a rather low concentration of proteins, and a large volume is often required. However, recent studies have shown the possibility of performing CSF glycoanalysis with a very small amount of fluid ( Cho et al, 2019 ). Increased levels of fucosylated and bisecting GlcNAc in AD CSF has been observed in several studies, which has also been confirmed in postmortem brains.…”
Section: Glycans As Biomarkers In Alzheimer’s Diseasementioning
confidence: 99%
“…One issue with this approach has been the fact that the CSF contains a rather low concentration of proteins, and a large volume is often required. However, recent studies have shown the possibility of performing CSF glycoanalysis with a very small amount of fluid ( Cho et al, 2019 ). Increased levels of fucosylated and bisecting GlcNAc in AD CSF has been observed in several studies, which has also been confirmed in postmortem brains.…”
Section: Glycans As Biomarkers In Alzheimer’s Diseasementioning
confidence: 99%
“…The native glycan is made less hydrophilic by the substitution of the hydrogen atoms in all hydroxyl, N ‐acetyl, and carboxylic acid moieties for methyl groups. Glycan permethylation is particularly efficient for the separation of isomers and, therefore, it is the most used derivatization technique for glycome analysis [3,7,11,16,20,82,84,85,95,96,138–142]. Otherwise, the use of permethylation in glycopeptides is not an easy task; to date, there is no reliable proof of its application [143].…”
Section: Glycan and Glycopeptide Derivatization Focused To Enhance Ismentioning
confidence: 99%
“…Genomics [ 3 ], transcriptomics [ 4 ], proteomics [ 5 ], glycoproteomics [ 6 ], metabolomics [ 7 ], lipidomics [ 8 ], and glycomics [ 9 ] are some of the omics analysis more often investigated by the researchers in the field. Recently, glycomic profiles of different human fluids such as blood, urine, saliva, and cerebrospinal fluid (CSF) have been associated with the progression of multiple diseases [ 10 , 11 , 12 , 13 , 14 ]. Both serum and plasma are the fluids of choice to perform glycomic analysis since unlike CSF, blood samples are easy to acquire.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the other above-mentioned human biofluids, CSF need a more invasive extraction procedure. Its direct contact with the brain and spinal cord makes this fluid a reliable analytical sample for the identification of biochemical changes that occur during the progression of neurodegenerative diseases [ 10 , 16 , 17 ]. Currently, CSF is a source of biomarkers for diagnostic workups of Alzheimer’s disease (AD), mild cognitive impairment (MCI), multiple sclerosis (MS), Parkinson’s, and other related diseases [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation